Teacher-Initiated, Student-Centered Global Education in a K to 8 School - Michael O'Sullivan; Diane Vetter (University of Windsor, 2007)
Despite a growing recognition that established notions of democracy, nationhood, citizenship, and ethnicity are giving way to emerging notions of democratic, multicultural, global citizenship, there are few curricular guidelines to achieve this expectation. This is especially the case at the elementary level where there isn't even a consensus that such an approach is appropriate. Faced with this lack of consensus and the resulting lack of curricular leadership and driven by the need to respond to the needs and interests of their students, elementary teachers, influenced by the particularities of their local circumstances, follow their instincts and rely on each other with respect to how to teach what is variously called global education, global citizenship education, or education from a global perspective. Elementary teachers are reshaping the practice of what is referred to in this paper as global (citizenship) education at the classroom level. While such innovations can frequently lead to creative results, they can also result in highly idiosyncratic interpretations of what constitutes the most effective approach to teaching from a global perspective or what constitutes global citizenship. This paper is a case study of the efforts of the staff of one small-town Ontario elementary school to infuse a global perspective throughout the grades from K to 8 and across the curriculum.